Developing weighting system for refurbishment building assessment scheme in Malaysia through analytic hierarchy process (AHP) approach - Kamaruzzaman, Syahrul Nizam; Lou, Eric Choen Weng; Wong, Phui Fung; Wood, Ruth; Che-Ani, Adi Irfan (Elsevier, 2018)
The building industry has an undeniable impact on the natural environment. Evidence shows that existing buildings make a significant contribution to energy demand and CO2 emissions. Refurbishing existing buildings offers significant opportunities to reduce energy consumption and CO2 emissions. The Malaysian government has set a target to retrofit 100 government buildings in order to contribute to the country's commitment to reduce the CO2 emissions intensity of gross domestic product by 45% by 2030. However, there is no specific sustainability assessment scheme targeted at building refurbishment in Malaysia. Thus, this research aims to support the development of a refurbishment sustainability assessment scheme for Malaysia. The Analytic Hierarchy Process (AHP) method was adopted in order to rank assessment themes and identify the priorities of the study's participating stakeholders. The outcome is the Malaysian Refurbishment Assessment Scheme (MRAS), which includes a set of weightings and a classification system for the selected assessment themes and sub-themes. The methods and findings can be adapted for use by other practitioners to develop building assessment schemes in order to pursue the goals of sustainable development through refurbishment.